Antibacterial activity and antibacterial mechanism of flavaspidic acid BB against Staphylococcus haemelyticus - Jiaxin Liu; Ruijie Liu; Rongrong Deng; Shiqian Zheng; Zhibin Shen (BMC Microbiology, 2023)
Abstract Background Staphylococcus haemolyticus (S. haemolyticus) is the main etiological factor in skin and soft tissue infections (SSTI). S. haemolyticus infections are an important concern worldwide, especially with the associated biofilms and drug resistance. Herein, we investigated the inhibitory effect of Flavaspidic acid BB obtained from plant extractions on clinical S. haemolyticus strains and their biofilms. Moreover, we predicted its ability to bind to the protein-binding site by molecular simulation. Since the combination of Hsp70 and RNase P synthase after molecular simulation with flavaspidic acid BB is relatively stable, enzyme-linked immunosorbent assay (ELISA) was used to investigate Hsp70 and RNase P synthase to verify the potential antimicrobial targets of flavaspidic acid BB. Results The minimum inhibitory concentrations (MIC) of flavaspidic acid BB on 16 clinical strains of S. haemolyticus was 5 ~ 480 µg/mL, and BB had a slightly higher inhibitory effect on the biofilm than MUP. The inhibitory effect of flavaspidic acid BB on biofilm formation was better with an increase in the concentration of BB. Molecular simulation verified its ability to bind to the protein-binding site. The combination of ELISA kits showed that flavaspidic acid BB promoted the activity of Hsp70 and inhibited the activity of RNase P, revealing that flavaspidic acid BB could effectively inhibit the utilization and re-synthesis of protein and tRNA synthesis, thus inhibiting bacterial growth and biofilm formation to a certain extent. Conclusions This study could potentially provide a new prospect for the development of flavaspidic acid BB as an antibacterial agent for resistant strains.